Oculopharyngeal muscular dystrophy: phenotypic and genotypic studies in a UK population. - Hill, M; Creed, G; McMullan, T; Tyers, A; Hilton-Jones, D; Robinson, DO; Hammans, SR (2001)
Oculopharyngeal muscular dystrophy (OPMD) is an autosomal dominant disorder of late onset that commonly presents with ptosis and dysphagia. The genetic basis of the condition has been identified recently as a stable trinucleotide repeat expansion in exon 1 of the poly(A) binding protein 2 gene (PABP2), in which (GCG)(6) is the normal repeat length. The prevalence of OPMD is greatest in patients of French-Canadian origin. It is not clear if expansion repeat length is a reliable test in other populations. In this study, we analysed the phenotypic and genotypic characteristics of 31 patients with OPMD in the UK. Ptosis was the first reported symptom in two-thirds of the patients, and half of the subjects studied had evidence of ophthalmoplegia. All but one family had a pathological expansion in the PABP2 gene, ranging from (GCG)(8) to (GCG)(13). In contrast to the French-Canadian population, (GCG)(10) was almost as common as (GCG)(9), evidence against a strong founder effect in the UK population. There was a weak association between repeat length and age of disease onset. Patients with longer repeat lengths, such as (GCG)(13), developed severe limb weakness early in the disease. We were unable to detect the (GCG)(7) polymorphism in over 200 normal controls, suggesting that the frequency of this expansion is lower than that found in the French-Canadian population. One family was negative for the expansion. Affected members presented with the classical features of OPMD, namely ptosis, dysphagia and cytoplasmic inclusions on muscle biopsy, although with some atypical features, such as early age of onset, high serum levels of creatine kinase and a profound ophthalmoplegia. This family is an example of a GCG expansion-negative oculopharyngeal syndrome requiring further genetic investigation. We conclude that PABP2 analysis is a reliable non-invasive diagnostic test for OPMD in the UK population.